Cost-Effectiveness Analysis of Prostate Health Index in Decision Making for Initial Prostate Biopsy - Huang, Da; Yang, Xiaoqun; Wu, Yishuo; Lin, Xiaoling; Xu, Danfeng; Na, Rong; Xu, Jianfeng (Frontiers in Oncology, 2020)
Background Clinical studies have suggested that prostate health index (phi) outperforms prostate-specific antigen (PSA) tests in prostate cancer detection. The cost-effectiveness of phi with different cutoffs is poorly understood in the context of decision making for prostate biopsy. Methods In a multicenter cohort, 3,348 men with elevated total PSA (tPSA) underwent initial prostate biopsy from August 2013 to May 2019. We constructed a decision model to evaluate the incremental cost-effectiveness ratios of different phi cutoffs. Total costs and reimbursement payments were based on the fee schedule of Shanghai Basic Medical Insurance and converted into United States dollars (). Two willingness-to-pay thresholds were estimated as one or three times the average gross domestic product per capita of China (7,760 or 23,279, respectively). Results The total costs of prostate biopsy and PSA tests were estimated at 315 and 19, respectively. The cost of phi test varied between 72 to 130 in different medical centers. Under different phi cutoffs (from 23 to 35), phi test predicted reductions of 420 (21.7%) to 972 (50.2%) in unnecessary biopsies, with a total gain of 23.77–57.58 quality adjusted life-years compared to PSA tests. All the cutoffs would be cost-effective for patients with tPSA levels of 2–10 ng/ml. Applying 27 as the cutoff was cost-effective for each tPSA range, with missing positive cases ranging from 11 (3.4%) to 33 (11.5%). Conclusions Using phi test was cost-effective in the decision-making process for initial prostate biopsy, especially for patients with tPSA values between 2–10 ng/ml. The phi cutoff of 27 was cost-effective regardless of tPSA ranges and should be recommended from a health-economic perspective.